THE STUDY OF PRIMARY SCHOOL ENGLISH TEACHERS' UNDERSTANDING OF THE ENGLISH CURRICULUM ON THE KURIKULUM MERDEKA - Lantika Vidara Handini, - (2023)
Kurikulum Merdeka (formerly known as the prototype curriculum) was designed as part of the learning recovery efforts as a more flexible curriculum framework, emphasizing critical elements and developing students' personalities and skills. Therefore, the current research aimed to investigate the primary school English teachers' understanding of the English Curriculum on the Kurikulum Merdeka. Since the teacher is a crucial element in achieving educational goals regarding teaching and learning activities, their understanding of the curriculum must be investigated. At the time of research, two private primary school English teachers in different schools in Bandung with students aged 9-12 years were chosen as research participants. A series of structured and unstructured interviews, classroom observations, and documentation were done to collect the data, which were then analyzed with triangulation technique analysis. The finding showed that all participants claimed to understand the English Curriculum on the Kurikulum Merdeka. However, in implementing the curriculum, the participants found teaching and learning activities in English classrooms challenging for several reasons. This demonstrates a need for a teacher training program for primary school English teachers related to the Kurikulum Merdeka guidelines.